Communication Patterns and User Behavior in the Digital Marketplace: A Bibliometric Review - Hasim; Miftakhul Fikri (INJECT (Interdisciplinary Journal of Communication), 2026)
Advances in digital technology have reshaped mediated communication patterns between brands and audiences, particularly through the convergence of e-commerce platforms like Shopee and video-based social media platforms like TikTok, which now serve as interactive communication ecosystems where persuasive narratives and social meanings are negotiated. This study aims to map the development of scientific research on communication patterns and user behavior on both platforms between 2021 and 2025 using a bibliometric approach. Through analysis of Scopus data filtered with PRISMA flowcharts and visualized using RStudio (Biblioshiny) and VOSviewer, a significant surge in publications was found, from 42 articles in 2021 to 188 articles in 2024. The dominance of keywords such as social media engagement, digital persuasion, and audience behavior indicates that communicative processes are central to shaping user responses. Conceptual mapping reveals that this study increasingly intersects with new communication technologies such as artificial intelligence and algorithms, signaling a shift towards data-driven, personalized communication strategies. From a communication science perspective, this study asserts that Shopee and TikTok operate as mediated spaces that redefine the construction of trust, identity, and digital rhetoric in the contemporary media ecosystem.